PERTANGGUNGJAWABAN PERTANGGUNGJAWABAN PIDANA WANITA YANG TERLIBAT DALAM PEREDARAN GELAP NARKOTIKA DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Sinaga, Lepina Rotua; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Narcotics is a very complex issue because it is a disease that is difficult to eradicate society, in Pekanbaru City narcotics today not only performed by men only, but women are also involved in drug trafficking perpetrators. Even cases increased from 2010 to 2013. Narcotics in criminal responsibility, the perpetrators of the crime of violation of sanctions imposed as punishment for his actions. As for the objectives of this thesis are: First, to determine the criminal liability of women involved in the illicit trafficking in jurisdictions Pekanbaru City Police. Second, to determine the criminal liability barriers women involved in the illicit trafficking in jurisdictions Pekanbaru City Police. Third, to determine the efforts made to overcome the obstacles in the criminal responsibility of women involved in the illicit trafficking in jurisdictions Pekanbaru City Police. This type of research is juridical sociological research, sources of data used, the primary data and secondary data, data collection techniques in this study with questionnaires, interviews and literature study.From the research, there are three main problems that can be concluded First, the criminal responsibility of women involved in drug trafficking in the city of Pekanbaru mostly put to Article 112, 114, 127 of Law No. 35 of 2009 on Narcotics. Second, obstacles to the criminal liability of women involved in the illicit trafficking in Pekanbaru, the lack of quantity and quality of factors investigator, factors less implementation of preventive police duties, lack of community participation factors and facilities. Third, efforts were made to overcome obstacles in the criminal responsibility of women submission of additional personnel and improve the quality of the investigator investigator, increase patrols and raids against narcotic crime scene, police officers provide counseling and legal understanding narcotic crime and maximization of existing infrastructure. Advice Author, First, the Pekanbaru City Police should be more regular in performing preventive and repressive tasks. Second, Pekanbaru City Police with the body of prison administrators should be more collaboration in the development of the filing of the request to the Department of Corrections Women's Law and Human Rights. Third, legal counseling activities undertaken Pekanbaru City Police force should be more improved